Working on the Railroad, Walking in Beauty Navajos, Hozho, and Track Work - Youngdahl, Jay (Utah State University Press, 2011)
"A valuable account of how the Navajo involvement in railroad labor and underlying cultural values interface. It is the sensitivity to that cultural identity that gives the work a special edge and at the same time a broad appeal. It is extremely well written and well organized. Jay Youngdahl tells a good story while applying high standards of scholarship along with an underlying humanism." Paul Zolbrod, author/translator of Din Bahan: The Navajo Creation Story. For over one hundred years, Navajos have gone to work in significant numbers on Southwestern railroads. As they took on the arduous work of laying and anchoring tracks, they turned to traditional religion to anchor their lives. Jay Youngdahl has used oral history and archival research to write a cultural history of Navajos' work on the railroad and the roles their religious traditions play in their lives of hard labor away from home.